Konseling untuk Meningkatkan Efikasi diri Siswa SMA Muhammadiyah Sewon dalam Menghafalkan Al-Qur’an - Estuningrum; Nurjannah Nurjannah (Universitas Islam Ahmad Dahlan, 2023)
This research is motivated by the phenomenon of the proliferation of tahfidz programs in various schools, especially madrasas where students there come from a variety of different cultures. Cultural diversity not only shows cultural richness, differences in student growth and development environments trigger the emergence of prejudices that lead to delays in the learning process, less than optimal achievement and even mental stress experienced by students. This study uses a quantitative approach and a descriptive method of development (research and development) which is directed as a process used to develop and validate educational products (Borg and Gall, 1989). The product of this research is a personal social guidance and counseling program to improve students' adjustment abilities. This research was conducted at Sewon Muhammadiyah High School, Bantul, which implemented a tiered Tahfidz curriculum. The population of this research is class II students. The results showed that the personal social guidance and counseling program was significantly able to improve students' self-adjustment abilities to the Tahfidz curriculum. That is, the programs compiled have been able to increase understanding and awareness and maximize the potential possessed by students. Keywords: Adjustment, Cultural Diversity, Guidance and Social Personal Counseling